Procalcitonin, Interleukin-6 and C-reactive Protein Levels Predict Renal Adverse Outcomes and Mortality in Patients with Acute Type A Aortic Dissection - Chen, Xuelian; Zhou, Jiaojiao; Fang, Miao; Yang, Jia; Wang, Xin; Wang, Siwen; Yang, Lichuan (Frontiers in Surgery, 2022)
Background: Acute type A aortic coarctation (AAAD) is a highly deadly and serious life-threatening disease. The purpose of this study was to estimate the predictive value of peak procalcitonin, interleukin-6, and C-reactive protein levels on adverse renal outcomes and mortality in patients undergoing surgery for AAAD. Methods: Perioperative peak PCT, CRP, and IL-6 levels were retrospectively collected in 331 patients hospitalized with AAAD from 2009 to 2021. The primary endpoints were AKI stage 2-3 and mortality. The receiver operating characteristic (ROC) curves were used to compare the predictive values of peak PCT, CRP, and IL-6 for different clinical outcomes. Multivariable logistic regression analysis was used to find risk factors for AKI and 30-day mortality. Results: The incidence of AKI stage 2-3 following AAAD was 50.8% (168/331). The 30-day and overall mortality were significantly greater in the AKI 2-3 group than in the AKI 0-1 group (P = 0.000). ROC curve analysis showed that peak PCT, with an area under the ROC curve (AUC) of 0.712, was a more accurate predictor of adverse renal outcomes than peak IL-6 and CRP. Multivariable logistic regression analysis revealed that PCT > 0.39 ng/ml was an independently risk factor for AKI stage 2-3. Peak IL-6 > 259 pg/ml was found to be an independent risk factor for 30-day mortality. Conclusion: In patients with surgery for AAAD, peak PCT provides a well-predictive indicator of AKI stage 2-3 and peak IL-6 indicates a favorable predictor of 30-day mortality.